Understanding the Process of Professionalisation in the Police Organisation. (June 2014) - Green, Tracey; Gates, Alison
The push toward professionalisation of policing is an expanding discourse in western societies. Professions, as opposed to trades, crafts or occupations, have particular characteristics, some of which have eluded policing and must be considered if the police are to reach this goal. Characteristics of a profession include a professional association, cognitive base, institutionalised training, licensing, work autonomy, colleague control, a code of ethics and high standards of professional and intellectual excellence. Further, professionalisation requires the alignment of various aspects of professional practice (Schneider, 2009). Tertiary education and the development of a body of discipline knowledge through research are crucial components of this. This paper examines some of the issues which have previously prevented police adopting a full professional model. It also examines the increasing involvement in the university sector by the police practitioner, which would seem to indicate some 'light at the end of the tunnel' and room for optimism for the future.